Synthesis and physical-chemical properties of 3-benzyl-8-(5-mercapto-4-phenyl-[1,2,4]-triazole-3-ylmethylthiomethyl)xanthine and its s-substituted derivatives - K. V. Аleksandrova; A. S. Shkoda; S. V. Levich; M. V. Dyachkov; D. M. Yurchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Aim. Currently, researches, devoted to obtain new active compounds, are carried out among various classes of organic compounds, and combination of several active heterocyclic fragments in one molecule is considered the key way in such researches.